Detection of West Nile virus in six mosquito species in synchrony with seroconversion among sentinel chickens in India. Issue 1 (December 2017) - Khan, Siraj; Chowdhury, Purvita; Choudhury, Parveena; Dutta, Prafulla
Abstract Background West Nile virus (WNV) is a zoonotic flavivirus maintained in mosquito-bird transmission cycle. Although humans are accidental hosts, fatal outcomes following WNV infection have been reported from India. Studies have identified WNV as an important etiological agent causing acute encephalitis syndrome in Assam, Northeast India. While circulation of WNV is evident, the role of vectors and avian hosts involved in the transmission remains unclear. In this study we identified local mosquito species for evidence of WNV infection along with seroconversion among sentinel chickens. Methods Mosquitoes were collected and pooled species wise from June 2014 through December 2015. Virus was screened using reverse transcriptase PCR followed by sequencing and phylogenetic analysis. Sentinel chicken blood was screened for WNV antibody to assess their role in WNV transmission. Results A total of 52, 882 mosquitoes belonging to 16 species were collected. WNV was detected in 18 pools ofCulex vishnui, Culex tritaeniorhynchus, Culex quinquefasciatus, Culex whitmorei, Culex pseudovishnui andMansonia uniformis. Phylogenetic analysis revealed that all mosquito derived sequences belonged to Lineage 5 and were 99–100% similar to the Assam strain of WNV isolated from human CSF sample in 2007. All sentinel chickens had seroconverted by the month of July that happens to be the peak WNV transmission month among humans as well. Conclusion To the best of our knowledge, this is the first report of WNV identification from field-collectedCx. pseudovishnui andMansonia uniformis in India. Our study demonstrates potential vectors which may play a crucial role in WNV transmission and should be considered in the vector control strategies. Additionally, our study highlights the role of sentinel chickens for WNV surveillance.